Sexual Harassment and its Implication on Employeeâs Performance in Sabah, Malaysia - Sarjono, Fauzie; Omar, Marja Azlima (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: The aim of this study is to identify the relationship between sexual harassment and its implication on employeeâs performance in one of Sabahâs informal sector. The independent variables of this study are sexual coercion and sexual annoyance. In order to analyze the data, this study employs regression analysis. Likert Scale is in turn used to measure the respondentsâ perceptions on sexual harassment at workplace. Survey and interview are the other two methods used in this study. The findings show that there is a significant relationship in a negative direction between sexual harassment and employeesâ performance. In other words, sexual harassment at work place does profoundly affect workersâ performances. This study also finds that gender plays a significant factor as female respondents tend to indicate particularly higher regards on sexual harassment. It is hoped that the findings of this study could contribute to alleviate if not to resolve the problems of sexual harassment at workplace. In the concluding remarks, this paper seeks to outline some suggestions to improve employeesâ efficacy in the organization which performance is hampered by occurrence of sexual harassment.Key words: sexual harassment, employeeâs performance, Sabahâs informal sector, and improve employeesâ efficacy.===About the Author: Fauzie Sarjono and Marja Azlima Omar are Lecturers at the Industrial Relation Programme, School of Social Sciences UMS (University of Malaysia Sabah), Locked Bag 2073, 88999 Kota Kinabalu, Sabah, Malaysia. For academic purposes, they can be reached at: fauzie@ums.edu.my and marjalina@asia.comHow to cite this article? Sarjono, Fauzie & Marja Azlima Omar. (2010). âSexual Harassment and its Implication on Employeeâs Performance in Sabah, Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.3, No.1 [Mei], pp.95-108. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (February 19, 2010); Revised (March 23, 2010); and Published (May 20, 2010). Â Â